Social constructions of migration in Nigeria and Zimbabwe : discourse, rhetoric, and identity - Oparinde, Kunle Musbaudeen; Makombe, Rodwell (Diverse perspectives on creating a fairer society, 2024)
Human movement and mobility are at an all-time high, making it more important than ever to understand how discourses around migration shape and influence individuals and the socioeconomic conditions of the countries they both inhabit and leave behind. Featuring both intercontinental and intracontinental perspectives, authors Kunle Musbaudeen Oparinde and Rodwell Makombe present new, much-needed data from the African continent in terms of how discourses around migration are socially constructed in Africa and how this compares globally. Collected from social media and online platforms, this data spotlights the everyday realities of Nigerians and Zimbabweans, and by extension many Africans, in their quest to relocate. Unpacking reasons for migration, as well as the dominant discourses post-migration, the authors analyse the inherent feelings of migrants, potential migrants, unwilling but forced migrants and those who have chosen to remain in their countries despite harsh socioeconomic realities. Examining this pressing field of study in an underexplored regional context, Social Constructions of Migration in Nigeria and Zimbabwe takes a refreshing new angle to deepen our understanding around the causes and effects of migration.